Dawn and the impossible three - Martin, Ann M., 1955- (Martin, Ann M., 1955- Baby-sitters Club, 2020)
As a new member of the Baby-sitters Club, Dawn tries to win the acceptance of the club's president by tackling a tough babysitting job.